2022
DOI: 10.1111/jzo.12979
|View full text |Cite
|
Sign up to set email alerts
|

Too cool to fight: Is ambient temperature associated with male aggressive behavior in the mesquite lizard?

Abstract: Aggressive behavior is performed in the context of intraspecific competition for gaining access to mates, food, or suitable territories. However, aggressive confrontations may divert time and energy from other important activities and increase the likelihood of suffering physical injury or predation. Aggressive behavior is particularly costly for ectotherms because it may reduce the time available for thermoregulation, which is a time‐consuming activity but indispensable for adequate maintenance of metabolic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…The mesquite lizard experiences different environmental conditions across its wide geographic distribution, which have promoted morphological, behavioural and physiological changes at the population level (Domínguez‐Godoy et al., 2022; González‐Morales, Rivera‐Rea, Moreno‐Rueda, Bastiaans, Díaz‐Albiter, et al., 2021; Plasman et al., 2020). These changes allow it to survive in diverse landscapes, including thermally unfavourable ones, such as mountain highlands (Domínguez‐Godoy, Gómez‐Campos, et al., 2020; Plasman et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mesquite lizard experiences different environmental conditions across its wide geographic distribution, which have promoted morphological, behavioural and physiological changes at the population level (Domínguez‐Godoy et al., 2022; González‐Morales, Rivera‐Rea, Moreno‐Rueda, Bastiaans, Díaz‐Albiter, et al., 2021; Plasman et al., 2020). These changes allow it to survive in diverse landscapes, including thermally unfavourable ones, such as mountain highlands (Domínguez‐Godoy, Gómez‐Campos, et al., 2020; Plasman et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sceloporus grammicus is capable of inhabiting agricultural zones, where it can exhibit high abundances (Pérez‐Mendoza et al., 2013, 2014). Likewise, some studies have shown that the thermal quality of the habitat and the thermoregulatory efficiency of this lizard are higher in agricultural areas in comparison with forest or high‐altitude grassland zones (Díaz de la Vega‐Pérez, Barrios‐Montiel, et al., 2019; Domínguez‐Godoy et al., 2022). Additionally, various studies about physiological aspects of S. grammicus have been done in mountains located in the Trans‐Mexican Volcanic Belt system (TMVB; González‐Morales, Rivera‐Rea, Moreno‐Rueda, Bastiaans, Castro‐López, & Fajardo, 2021; González‐Morales, Rivera‐Rea, Moreno‐Rueda, Bastiaans, Díaz‐Albiter, et al., 2021; González‐Morales et al., 2023; Plasman et al., 2020; Rivera‐Rea et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The viviparous lizard S. grammicus has developed adaptations to harsh environmental conditions in the high mountains of central Mexico. These adaptations include changes in morphology, physiology, behavior, intestinal microbiome, and life history ( 80 , 94 97 ). Evidence from other Sceloporus species indicates that adaptations in the placenta may allow for the exchange of nutrients to keep embryos developing under restrictive environmental conditions ( 98 ).…”
Section: Discussionmentioning
confidence: 99%